LTr1 alleviates DSS-induced ulcerative colitis by modulating macrophages to inhibit M1 polarization and associated inflammatory responses - Zhu, Wenjing; Cheng, Qian; Liu, Chang; Qian, Jiacheng; Xu, Jia; Wang, Xinyuan (Frontiers in Immunology, 2025)
IntroductionUlcerative colitis (UC) is a chronic inflammatory bowel disease marked by recurrent mucosal inflammation, leading to symptoms such as bloody diarrhea and weight loss, which severely impair patients’ quality of life. Current treatments are often limited by long-term efficacy and safety concerns. LTr1, a trimeric compound derived from indole-3-carbinol (I3C), has shown anti-cancer potential, but its role in inflammatory diseases remains unclear. This study aims to investigate the protective effects and underlying mechanisms of LTr1 in a dextran sulfate sodium (DSS)-induced colitis mouse model.MethodsUC was induced by administering 2.5% DSS in drinking water for 7 days, while LTr1 was orally administered at 100 mg/kg daily starting from day 1. Clinical symptoms, histological changes, and pro-inflammatory cytokine levels in the colon and serum were assessed. Macrophage infiltration and polarization in the colon and spleen were analyzed by flow cytometry and qPCR. In vitro, the direct effects of LTr1 on macrophage polarization were examined using CCK-8, flow cytometry, and qPCR. Network pharmacology was employed to explore potential molecular mechanisms.ResultsLTr1 significantly alleviated clinical symptoms, reduced histological damage, preserved intestinal barrier integrity, and suppressed the production of inflammatory cytokines. It also inhibited DSS-induced macrophage infiltration and M1 polarization in vivo. Moreover, LTr1 directly and effectively suppressed LPS-induced M1 macrophage polarization in vitro. Finally, network pharmacology analysis identified TP53, AKT1, HSP90AA1, EGFR, and SRC as potential targets of LTr1 in the context of UC.ConclusionThese findings indicate that LTr1 exerts protective effects against DSS-induced colitis, at least in part by inhibiting macrophage infiltration and M1 polarization, thereby reducing pro-inflammatory cytokines production. This study provides a theoretical foundation for optimizing UC treatment strategies and highlights LTr1 as a promising candidate for the development of novel UC therapies.